MENUMBUHKAN SIKAP TOLERANSI SISWA MELALUI MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI MADRASAH IBTIDAIYAH - Andina Halimsyah Rambe; Megawati Mahalil Asna (Universitas Islam Malang, 2022)
Tolerance is a human nature to respect each other that respects that exists, between individuals or groups. Tolerance behavior is so meaningful to be fostered in the school environment, at least every student has positive behavior in different ethnic cultures. Parents and educators have an important responsibility to develop tolerance in the hearts of students. This research was conducted by measuring the size of the attitude of tolerance among students. This study aims to examine the importance of an MI teacher to foster tolerance among students at school. So with a study on fostering an attitude of tolerance towards students, it can make them more respectful of one another, not cornering each other, and respecting the opinions of others, and so on. The method and approach in this research is a library research approach. Literature study is an activity where data collection is carried out from various sources such as books, journals and others. There are four actions in conducting this library research, namely: First, the researcher conducts research through text or data in the form of numbers. Second, researchers only deal directly with reading materials in the library. Third, the library data comes from the second party not from the first party or from the field directly and generally comes from secondary data. Fourth, the state of the library data is not limited by time and place, so it is easy to find the data.